2011
DOI: 10.1128/jcm.05459-11
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs in Patients with Active Pulmonary Tuberculosis

Abstract: Emerging evidence shows that microRNAs (miRNAs) play an important role in pathogen-host interactions. Circulating miRNAs have been repeatedly and stably detected in blood and hold promise to serve as molecular markers for diverse physiological and pathological conditions. To date, the relationship between circulating miRNAs and active pulmonary tuberculosis (TB) has not been reported. Using microarray-based expression profiling followed by real-time quantitative PCR validation, the levels of circulating miRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
180
5
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(206 citation statements)
references
References 32 publications
15
180
5
6
Order By: Relevance
“…Along the same line, miR-29a was upregulated in both serum and sputum of patients with active pulmonary tuberculosis compared with the levels in healthy controls. 76 Opposite to the above observed induction of miR-29, it was shown that activated T cells of mice infected with M. bovis bacillus Calmette-Guerin (BCG) presented lower expression levels of miR-29 than the cells of their non-infected littermates. 73 This inhibition of miR-29 facilitated IFNγ production by the T cells and, accordingly, transgenic mice expressing a "sponge" designed to compete with endogenous miR-29 showed a greater resistance to infection with BCG or M. tuberculosis.…”
Section: Emerging Principles and Open Questionsmentioning
confidence: 99%
“…Along the same line, miR-29a was upregulated in both serum and sputum of patients with active pulmonary tuberculosis compared with the levels in healthy controls. 76 Opposite to the above observed induction of miR-29, it was shown that activated T cells of mice infected with M. bovis bacillus Calmette-Guerin (BCG) presented lower expression levels of miR-29 than the cells of their non-infected littermates. 73 This inhibition of miR-29 facilitated IFNγ production by the T cells and, accordingly, transgenic mice expressing a "sponge" designed to compete with endogenous miR-29 showed a greater resistance to infection with BCG or M. tuberculosis.…”
Section: Emerging Principles and Open Questionsmentioning
confidence: 99%
“…Several studies suggest that key TBprotective cytokines, including TNF-α and IFN-γ, are regulated by miR-125b and miR-29, respectively (16,17). Moreover, screening approaches have tentatively pointed to miRNA signatures characteristic of active TB (18)(19)(20)(21)(22). Yet, no functional role in TB for any of these miRNAs has been elucidated, including the effects on chemokines and cell migration.…”
Section: Introductionmentioning
confidence: 99%
“…They are recognized as important regulators of biological processes including T cell-and B cell-mediated immune responses and other immune functions (13,14). Studies of natural infection with influenza, Mycobacterium tuberculosis, and HIV have suggested that miR profiling studies can identify biomarkers of infection and predictors of clinical outcome (15)(16)(17)(18). However, the expression profile of host miRs during Plasmodium infection in humans has not yet been investigated and their ability to act as biomarkers for infection and/or immune control remains unknown.…”
Section: Introductionmentioning
confidence: 99%